Mindfulness skills and experiential avoidance as therapeutic mechanisms for treatment-resistant depression through mindfulness-based cognitive therapy and lifestyle modification - Garcia-Toro, Mauro; Aguilar-Latorre, Alejandra; Garcia, Aurora; Navarro-Guzmán, Capilla; Gervilla, Elena; Seguí, Andrea; Gazquez, Francisco; Marino, Jose Antonio; Gomez-Juanes, Rocío; Serrano-Ripoll, María J.; Oliván-Blázquez, Bárbara; Garcia-Campayo, Javier; et al. (Frontiers in Psychology, 2023)
Background/objective The COVID-19 pandemic and consequent physical distancing has made it difficult to provide care for those with Treatment-Resistant Depression (TRD). As a secondary analysis of a clinical trial, the aim of this study was to explore potential mechanisms through which three online-delivered approaches, added to treatment as usual, improve depressive symptoms in TRD patients. Methods The three approaches included (a) Minimal Lifestyle Intervention (MLI), (b) Mindfulness-Based Cognitive Therapy (MBCT), and (c) Lifestyle Modification Program (LMP). Sixty-six participants with TRD completed assessments pre-post intervention (mindfulness skills [FFMQ]; self-compassion [SCS]; and experiential avoidance [AAQ-II]) and pre-intervention to follow-up (depressive symptoms [BDI-II]). Data were analyzed using within-subjects regression models to test mediation. Results Mindfulness skills mediated the effect of MBCT on depressive symptoms (ab = −4.69, 95% CI = −12.93 to−0.32), whereas the lack of experiential avoidance mediated the effect of LMP on depressive symptoms (ab = −3.22, 95% CI = −7.03 to−0.14). Conclusion Strengthening mindfulness skills and decreasing experiential avoidance may promote recovery in patients with TRD, MBCT, and LMP have demonstrated that they may help increase mindfulness skills and decrease experiential avoidance, respectively. Future work will need to unpick the components of these interventions to help isolate active ingredients and increase optimization.